EPIDEMIOLOGICAL PROFILE OF SNAKEBITE ACCIDENTS IN A METROPOLITAN AREA OF NORTHEAST BRAZIL - Albuquerque, Polianna L.M.M.; Silva Junior, Geraldo B.; Jacinto, Camilla N.; Lima, Caroline B.; Lima, Juliana B.; Veras, Maria do Socorro B.; Daher, Elizabeth F. (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
SUMMARY The aim of this study was to describe the epidemiological profile of snakebite accidents reported by the toxicological assistance center in Fortaleza, Ceará, Brazil. Database information on snakebite accidents was analyzed regarding the period from January 2003 to December 2011. A total of 1063 cases were found. The accidents occurred during the rainy months (March, April and May), in urban areas (52.3%), affecting individuals younger than 50 years and predominantly among males (70.7%). The lower limbs were the most frequently affected body area (33.7%). Most accidents involved non-venomous snakes (76.1%). The genus Bothrops was the main one involved in venomous accidents (83%). It is expected that this study can be used as the substrate to improve healthcare surveillance and implementing better measures for the treatment of this population.